Some Contributions to the Legend of Etana - Kinnier Wilson, J. V.
I. The Introduction; II. The Beginning of Tablet II; III. The Eagle’s Dream; IV. The Birth of a Son. New Texts: Sm 1839, 83-1-18, 489, Sm 157 + 1134; new copy: K. 2606.